Pengoptimuman parameter pengacuan bagi mengurangkan kecacatan jasad anum proses pengacuan suntikan logam (MIM) - Jamaludin, Khairur Rijal (The Institution of Engineers, Malaysia, 2008)
Injection molding parameters of the metal powder mixture has been optimized using L27 (313) orthogonal array. Parameters optimized were injection pressure, injection temperature, powder loading, mold temperature, holding pressure and injection speed. Metal powder mixture used is a bimodal SS316L, and polyethylene glycol (PEG), polymethyl methacrylate (PMMA) and stearic acid as binder. Beside those, interactions of the injection pressure, injection temperature and powder loading were studied. Pareto-Anova analysis for the smallest the best signal to noise ratio (S/N) presents the significance of each parameters and interactions. Results shows that the interaction between injection pressure and temperature has highest significant percentage (19.39 %) followed by interactions between injection pressure and power loading (17.77 %) and, injection temperature and powder loading (14.41 %). Beside those, injection rate was the single parameter that greatly influences the green part defects of 14.41 %, while injection pressure and holding pressure were less significant of about 0.27 % and 0.58 % respectively. Results shows that the optimum injection parameter was as follows: 350 bar (injection pressure); 150 oC (injection temperature); 64 % volume (powder loading); 51 oC (mold temperature); 700 bar (holding pressure); and 15 ccm/s (injection rate). Signal noise ratio at the optimum condition was -2.46 dB ï‚±2.05 at 90 % confidence interval. The optimum parameter has been confirmed by the confirmation experiment to ten samples and its signal noise ratio obtained was -255 dB which was within the optimal range.